The varieties of pension governance pension privatization in Europe - Ebbinghaus, Bernhard (Oxford : Oxford University Press, 2011)
Sustainable and adequate old age pensions in ageing societies have become a major topic on the political agenda. This book describes the shift from public to private pensions and explains the differences across ten European countries.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Old age pensions -- Europe; Old age pensions -- Government policy -- Europe; Pension trusts -- Investments -- Europe